ADMINISTRATIVE CORRUPTION AND GOOD GOVERNANCE IN IRAQ: FINDING AND ANALYSIS - Bin Ismail, Ibrahim; Abbas, Rafid Ali (European Scientific Journal, ESJ, 2015)
The good governance in Iraq can only be achieved when the corruption in the public sector is eliminated. This can be achieved only when there is an equality at work among the public servants in order for them to achieve job satisfaction in terms of their salaries and job description. It was found that job satisfaction is the main factor that contributes to the reduction of corruption. This article discusses the relationship between good governance and the administrative corruption. It outlines the findings and results that have been done among public servants. This study was made possible by all the public servants who have contributed to the findings by filling up the questionnaires which reflected real opinions and thoughts on corruption and the effort towards good governance in Iraq. The survey participants also left valuable feedbacks with regard to the questions. The feedbacks were very useful as more insights gained on the applications of good governance in Iraq and the quest for seeking real and conceptual reasons corruption takes place in Iraq.